Combining MK626, a novel DPP-4 inhibitor, and low-dose monoclonal CD3 antibody for stable remission of new-onset diabetes in mice. - Lei Ding; Conny A Gysemans; Geert Stangé; Yves Heremans; Yixing Yuchi; Tatiana Takiishi; Hannelie Korf; Marie Chintinne; Richard D Carr; Harry Heimberg; Daniel Pipeleers; Chantal Mathieu (PLoS ONE, 2014)
Combining immune intervention with therapies that directly influence the functional state of the β-cells is an interesting strategy in type 1 diabetes cure. Dipeptidyl peptidase-4 (DPP-4) inhibitors elevate circulating levels of active incretins, which have been reported to enhance insulin secretion and synthesis, can support β-cell survival and possibly stimulate β-cell proliferation and neogenesis. In the current study, we demonstrate that the DPP-4 inhibitor MK626, which has appropriate pharmacokinetics in mice, preceded by a short-course of low-dose anti-CD3 generated durable diabetes remission in new-onset diabetic non-obese diabetic (NOD) mice. Induction of remission involved recovery of β-cell secretory function with resolution of destructive insulitis and preservation of β-cell volume/mass, along with repair of the islet angioarchitecture via SDF-1- and VEGF-dependent actions. Combination therapy temporarily reduced the CD4-to-CD8 distribution in spleen although not in pancreatic draining lymph nodes (PLN) and increased the proportion of effector/memory T cells as did anti-CD3 alone. In contrast, only combination therapy amplified Foxp3+ regulatory T cells in PLN and locally in pancreas. These findings open new opportunities for the treatment of new-onset type 1 diabetes by introducing DPP-4 inhibitors in human CD3-directed clinical trials.